2020
DOI: 10.1093/cid/ciaa188
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Diagnosis of Progressive Pulmonary and Disseminated Coccidioidomycosis

Abstract: Background Antibody detection is the main method for diagnosis of coccidioidomycosis, but it has limitations. The Coccidioides antigen enzyme immunoassay is recommended for testing cerebrospinal fluid in suspected meningitis. Reports on urine and serum antigen detection evaluated small numbers of patients who were mostly immunocompromised. The purpose of this study was to assess the accuracy of combined antibody and antigen detection for diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Previous studies with the classical CF antibody test on CSF have reported false negative results that range from 17–41% [ 14 , 15 , 16 ]. A recent study [ 17 ] found CSF CF antibody testing to be 70% sensitive and 100% specific, virtually identical to what we found ( Table 4 a) with our specimens and assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with the classical CF antibody test on CSF have reported false negative results that range from 17–41% [ 14 , 15 , 16 ]. A recent study [ 17 ] found CSF CF antibody testing to be 70% sensitive and 100% specific, virtually identical to what we found ( Table 4 a) with our specimens and assays.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have information on the level of CSF inflammation (CSF leukocytes, protein, glucose) in almost all specimens, to correlate with our test results. To date, testing sera in coccidioidal antibody and antigen assays [ 16 , 22 ] has suggested only histoplasmosis presents a significant cross-reaction problem, but meningitis in histoplasmosis is a rare event; more data about performance of the tests studied here in other CNS mycotic infections would still be of interest. Data-gathering addressed to these shortcomings can be derived in future studies, and inform them.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple serological tests are available for IgM, IgG, or complement-fixing antibodies, as well as an enzyme-linked immunoassay that uses proprietary coccidioidal antigens. However, these tests lack sensitivity for coccidioidomycosis (5,6). Due to the difficulty in diagnosing Valley fever, it is often mistaken for bacterial pneumonia and inappropriately treated with antibiotics (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple serological tests are available for IgM, IgG, or complement-fixing antibodies, as is an enzymelinked immunoassay that uses proprietary coccidioidal antigens. However, these tests lack sensitivity for coccidioidomycosis (5,6). Due to the difficulty in diagnosing Valley fever, it is often mistaken for bacterial pneumonia and inappropriately treated with antibiotics (7)(8)(9)(10), and the lack of a suitable diagnostic strongly contributes to an unacceptably long 23-day median time to diagnosis (2).…”
mentioning
confidence: 99%